2009
DOI: 10.1111/j.1524-4733.2009.00577.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Using Clinical Risk Factors with and without DXA for Osteoporosis Screening in Postmenopausal Women

Abstract: Funders should be careful in adopting a strategy based on CRFs alone instead of DXA plus CRFs. Only if DXA is not available, assessing CRFs only is an acceptable option in predicting a woman's risk of fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 54 publications
1
15
0
1
Order By: Relevance
“…The remaining studies considered either compliance or persistence or did not consider any aspect of nonadherence. When tested in sensitivity analyses, adherence did not affect the results considerably [38,42,46,51,53,54]. The conclusion of a negligible impact of medication adherence on the cost-effectiveness ratio, however, is debatable because in most studies not all aspects of adherence were taken into account.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…The remaining studies considered either compliance or persistence or did not consider any aspect of nonadherence. When tested in sensitivity analyses, adherence did not affect the results considerably [38,42,46,51,53,54]. The conclusion of a negligible impact of medication adherence on the cost-effectiveness ratio, however, is debatable because in most studies not all aspects of adherence were taken into account.…”
Section: Discussionmentioning
confidence: 79%
“…While one model [57] referred to a NICE model published in 2002, three models [50,52,55] referred to a reference model recommended by the IOF [27]. The models from Schousboe et al and Muller et al were published for the first time in 2007-2008 and resulted in three [8,41,46] and four [38,51,53,54] analyses, respectively. While about two-third of the analyses were based on Markov cohort models, one quarter was based on microsimulation models.…”
Section: Characteristics Of the Analysesmentioning
confidence: 97%
See 2 more Smart Citations
“…Six diagnostic papers indicated that Markov modelling is a useful approach to estimate transitions between different health states depending on diagnosis and treatment [38,46], with one study also including failure to diagnose as a decision outcome [47]. O'Connor and Knoblauch [48] described the use of reports, detailing the proportion of people diagnosed and the anticipated life expectancy as a result of diagnosis, to model cost effectiveness.…”
Section: Accounting For Distance From Outcomesmentioning
confidence: 99%